CROSS-SECTIONAL STUDY OF EFFICACY OF ALBENDAZOLE IN THE TREATMENT OF SOIL HELMINTHES INFECTED SCHOOL AGE CHILDREN IN PARTS OF ODEDA, OGUN STATE, NIGERIA (FULafia Journal of Science and Technology, 2020)
This study assessed the efficacy and safety of albendazole (ALB) amongst soil-transmitted helminth (STH) infected school aged children (SAC) cross-section ally in Odeda Local Government Area (LGA), Ogun State, Nigeria. Consented 485 pupils between the ages of 5 – 16 years were examined for STH infections using the Kato-katz technique at baseline. All consented SAC were treated to a single dose (400mg) of ALB. Closeended questionnaires on safety of ALB administered to SAC, 24 hours after ingestion. Stool samples werecollected at 3-weeks post treatment to re-examine for Egg Reduction Rate (ERR) and Cure Rate (CR). The results were analyzed using SPSS version 20 with Chi-square set at p = 0.05 to compare relationship between demography factors and prevalence. Of the 485 pupils, an overall prevalence of 138(28.5%) were found to be infected with various species of STH infections.
Keywords: Safety; Efficacy; Albendazole; Soil-transmitted helminths; School Aged Children; Odeda